Instantaneous GPS/Galileo/QZSS/SBAS Attitude Determination: A Single-Frequency (L1/E1)Robustness Analysis under Constrained Environments - Nadarajah, Nandakumaran; Teunissen, Peter (Institute of Navigation, Inc., 2014)
The augmentation of new global navigation satellite systems (GNSS) to existing GPS enhances the availability of satellite based positioning, navigation, and timing (PNT) solutions. Among existing systems, the European Galileo system, the Japanese quasi-zenith satellite system (QZSS), and satellite based augmented systems (SBAS) share at least one frequency (L1/E1) with GPS. In this contribution we analyse the robustness of single-frequency instantaneous carrier-phase attitude determination using data from some or all of the four systems GPS/Galileo/QZSS/SBAS. The performance of the constrained (C)-LAMBDA method is studied under various satellite deprived environments and compared to that of the standard LAMBDA method, using L1/E1 data that was observed for ten days at Curtin University, Perth, Australia. The results demonstrate the enhanced robustness that combinations of the four systems bring to single-epoch single-frequency attitude determination.